Rice (Oryza sativa L.) bran preserves cardiac function by modulating pro-inflammatory cytokines and redox state in the myocardium from obese rats - Garcia, Jéssica Leite [UNESP]; Vileigas, Danielle Fernandes; Gregolin, Cristina Schmitt [UNESP]; Costa, Mariane Róvero [UNESP]; Francisqueti-Ferron, Fabiane Valentini [UNESP]; Ferron, Artur Junio Togneri [UNESP]; De Campos, Dijon Henrique Salomé [UNESP]; Moreto, Fernando [UNESP]; Minatel, Igor Otávio [UNESP]; Bazan, Silméia Garcia Zanati [UNESP]; Corrêa, Camila Renata [UNESP] (Springer Nature, 2022)
Purpose: This study aimed to evaluate the effect of rice bran (RB) supplementation to a high-sugar fat (HSF) diet on cardiac dysfunction in an experimental obesity model. Methods: Male Wistar rats were distributed into three groups: control, high-sugar fat, and high-sugar fat supplemented with 11% RB for 20 weeks. Results: HSF diet promoted obesity and metabolic complications. Obese rats showed cardiac structural and functional impairment associated with high levels of interleukin-6, tumoral necrosis factor alpha, and malondialdehyde, and decreased activity of superoxide dismutase and catalase in the myocardium. RB supplementation was able to mitigate obesity and its metabolic alterations in HSF diet-fed animals. Moreover, the RB also prevented structural and functional damage, inflammation, and redox imbalance in the heart of these animals. Conclusion: This study suggests that RB supplementation prevents cardiac dysfunction in rats fed on HSF by modulating systemic metabolic complications and inflammation and oxidative stress in the myocardium, representing potential alternative therapy.
Keywords: Cardiac remodeling; Inflammation; Insulin resistance; Oxidative stress; Rice bran; Western diet